2017
DOI: 10.17116/jnevro20171179151-58
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of cavinton therapy regimen for infusions and cavinton comforte in acute and early recovery periods after ischemic stroke

Abstract: More rapid and complete regression of neurological deficit, better recovery of self-care function, cognitive function and social activity, an increase in erythrocyte membrane elasticity were found in the main group compared to the control one. These results indicate the efficacy of cavinton R and cavinton R comforte in the regimen used in complex treatment in acute and early recovery periods after ischemic stroke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
(14 reference statements)
0
4
0
Order By: Relevance
“…1 ). Ultimately, 17 articles were selected for full-text review, out of which four placebo-controlled RCTs were found to be eligible (one double-blind, one single-blind, and two open-label RCTs), enrolling a total of 601 and 236 patients in the vinpocetine and placebo groups, respectively [ 9 , 11 , 15 , 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 ). Ultimately, 17 articles were selected for full-text review, out of which four placebo-controlled RCTs were found to be eligible (one double-blind, one single-blind, and two open-label RCTs), enrolling a total of 601 and 236 patients in the vinpocetine and placebo groups, respectively [ 9 , 11 , 15 , 16 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…All these RCTs included patients with acute arterial ischemic stroke only. The cutoff time interval for enrolment in the study was between 24 h to 14 days in these RCTs, but all of them excluded patients with very severe arterial ischemic stroke, with high NIHSS scores (> 17 and > 25 in the study by Zhang et al [ 11 ] and Belova et al [ 15 ], respectively). All these RCTs excluded patients with significant coexistent other psychiatric disorders, dementia, severe, uncontrolled cardiac, renal, hepatic, or endocrinal impairment including myocardial infarction, and those with evidence of hemorrhage on neuroimaging.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Vinpocetine's most well-documented clinical use (indirect) has been in acute ischemic stroke, where it has been characterized as a neuroprotective agent. Over ten trials, including more than five randomized controlled trials, have been conducted in the past, and researchers have provided systematic reviews on vinpocetine's effectiveness [31][32][33][34][35]. However, the final verdict on its effectiveness still remains unclear.…”
Section: Vinpocetine-what Do We Know So Far?mentioning
confidence: 99%